A non-aseptic bioprocess for production and recovery of 2,3-butanediol via conversion of crude glycerol and corn steep liquor at pilot-scale - Dimitris Karayannis; Nikos Angelou; Gabriel Vasilakis; Ioannis Charisteidis; Alexandros Litinas; Seraphim Papanikolaou (Carbon Resources Conversion)
The production and recovery of 2,3-butanediol (BDO) through biodiesel derived glycerol valorization by Klebsiella oxytoca ACA-DC 1581 was holistically optimized with regard to the efficiency and cost of the bioprocess. The absence of thermal treatment of the substrate had no negative effect upon the growth of microorganism and the bioconversion of crude glycerol into BDO, enabling the development of a non-aseptic and lower-cost bioprocess. Both digestate and corn steep liquor (CSL), the main by-products of the biogas and corn industries respectively, successfully served as the sole source of nitrogen, contributing to the complete replacement of more expensive sources (e.g., yeast extract). The biochemical pathway of glycerol catabolism was examined under varying concentrations of dissolved oxygen and BDO production was optimized in a fully aerobic environment (volumetric mass transfer coefficient; kLa = 70.5 1/h.) The glycerol consumption rate was 2.80 g/L/h, the BDO productivity reached 1.12 g/L/h and the yield of BDO produced per unit of glycerol consumed was 0.46 g/g, with these values being among the highest ones reported in the literature for wild-type strains cultivated on crude glycerol. In all fed-batch fermentations, final BDO and acetoin concentration reached ∼80 g/L, while a plateau was observed at ∼68 g/L of BDO. Finally, the culture was carried out efficiently in the pilot-scale reactor (250 L). The salting-out extraction (SOE), consisting of ethanol (24 %) and K2HPO4 (25 %), recovered 91.7 % of BDO from the fermentation medium and was studied for the first time in a glycerol-based medium. The study suggests the potential industrialization of the bioprocess through sustainable, pilot-scale and low-cost bioconversion of biodiesel-derived crude glycerol and CSL or digestate into BDO.